Comparative effect of L-asparagine and sodium nitrate in inducing L-asparaginase production by endophytic Fusarium sp. - Hermanto, Alex; Su Yien Ting, Adeline (Acta Biologica Szegediensis, 2016)
This study investigated the effect of two nitrogen sources (L-asparagine and sodium nitrate) on L-asparaginase production by endophytic Fusarium sp. (R19). L-asparagine is the more expensive nitrogen source, while sodium nitrate is the cheaper alternative of them. The production of L-asparaginase was quantified via Nesslerization and optimum incubation period was determined at 5-day intervals for 20 days. Fungal biomass obtained from supplementation of these nitrogen sources were weighed and correlated to the L-asparaginase production via Pearson correlation. Results revealed that sodium nitrate was unfortunately, inferior to L-asparagine in inducing L-asparaginase production in isolate R19. Supplementation with 1.25% L-asparagine yielded more L-asparaginase (3.01 U/mL), while the addition of sodium nitrate produced significantly lower levels (0.65 U/mL). The optimum incubation period was 5 and 10 days with supplementation of sodium nitrate and L-asparagine, respectively. Production of L-asparaginase correlates strongly to the fungal biomass (r = 0.990) suggesting nitrogen source impacts fungal growth and biomass, which subsequently influenced L-asparaginase production. To summarize, production of L-asparaginase from R19 was optimum with supplementation of 1.25% L-asparagine, incubated for 10 days. Sodium nitrate, although it is relatively cheap, was not effective in inducing L-asparaginase production. Further optimization studies can be performed to produce more L-asparaginase.